CRUSTAL SHORTENING DURING MOUNTAIN BUILDING: A CASE STUDY IN THE PAMIR-TIEN SHAN AND ALTAY-MONGOLIA REGION - Yakovlev F.L.; Yunga S.L. (My University, 2001)
Unravelling the underlying causes of mountain building is one pivotal issue of geotectonics. The most popular model invokes crustal thickening through horizontal, across mountain ranges, contraction of the area occupied by a mountainous country with its ensuing isostatic uplift. Another model calls for crustal underplating due to either underthrusting or to melts derived from mantle plumes, also resulting, through isostatic mechanisms, in mountain building. The objective of this paper is to establish relations between these two likely processes using case studies from the Pamir-Tien Shan region, as well as Altay and Mongolia. In tackling this problem, two methods are employed to define the amount of crustal shortening. Method 1 draws on crustal thickness as a starting value, and shortening is calculated as a function of its increase relative to the initial "cratonic'' thickness. In contrast to well-known approaches, geometric characteristics of magnitudes of neotectonic movements used in this algorithm enable one to establish the direction of maximum shortening and the relation between maximum and minimum shortenings. A data base on Moho depths and neotectonic movement magnitudes from Tien Shan was used. The N-S crustal shortening was found to be between 12% and 25% for Tien Shan. Method 2 is a modification of routine calculations based on folding and faulting deformations of peneplanation surfaces. Shortening values thus obtained were 4-12% on average for Tien Shan, 35% to 60% for the Afghan-Tajik basin, and less than 1% for Pamir, whereas Altay, Sayan, and Mongolia yielded both extension and shortening of 0.1% to 1.2%. Comparison of crustal shortening values obtained for Tien Shan by the two different methods shows a match of results obtained from maximum shortening directions and from spatial distribution of shortening maxima. A good correlation of these values was established, which is interpreted to show the model of crustal shortening and thickening (Method 1) to be in keeping with the natural process. Analyzing the regression of paired shortening values shows that lack of shortening from peneplanation surface deformations corresponds to a crustal thickening of 7 km on average across Tien Shan. This is interpreted to suggest that, in Tien Shan, the two mountain building processes, horizontal shortening and crustal underplating, are in operation concomitantly. Therefore, one cause of mountain building in Tien Shan is pressure exerted by Pamir and Tarim and transmitted 300-400 km northward from their boundary. In Mongolia, Sayan, and Altay alike, mountain building might be driven by the same causes related to rifting. Crustal shortening data rule out any impact from the Indian subcontinent pressing northward.
Keywords: CRUSTAL SHORTENING; RIFTING; PLATE TECTONICS; UNDERPLATING